2003
DOI: 10.1080/08910600310016005
|View full text |Cite
|
Sign up to set email alerts
|

Oral Distribution of Genera, Species and Biotypes of Yeasts in Patients with Marginal Periodontitis

Abstract: Yeasts can be members of the commensal flora in the healthy human mouth. They have also been found in periodontal pockets of patients with marginal periodontitis, but little is known about their distribution in other oral sites of such patients. The aim of the present study was to examine the distribution of genera, species and biotypes of yeasts in various sites of oral cavities of patients with chronic marginal periodontitis. Samples were taken from the periodontal pockets, buccal mucosa and palate of 70 mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…The predominance of a single biotype of Candida albicans in candidal carriers, as noted here, has been reported previously (34)(35)(36)(37). Recently, Song et al reported three predominant biotypes of Candida albicans obtained from healthy subjects in Sweden, one of which was the same biotype as ours (7347340015) (12).…”
Section: Discussionsupporting
confidence: 87%
“…The predominance of a single biotype of Candida albicans in candidal carriers, as noted here, has been reported previously (34)(35)(36)(37). Recently, Song et al reported three predominant biotypes of Candida albicans obtained from healthy subjects in Sweden, one of which was the same biotype as ours (7347340015) (12).…”
Section: Discussionsupporting
confidence: 87%
“…Yeasts of the marginal periodontitis group were more genetically diverse than yeasts of the oral health group because of its larger S AB range, lower average S AB value and three unique genetic clusters in the pooled dendrogram. Yeasts of the same marginal periodontitis group also showed higher diversity in colony morphology and biotype than yeasts of the oral health group (3). This implies some association between yeast phenotype and genetic attributes in health and disease.…”
Section: Discussionmentioning
confidence: 95%
“…Yeasts are regarded as opportunistic commensals in the human mouth. Mucosal surfaces are the primary oral body reservoirs for these microorganisms (1–3). Yeasts can also be found in dental plaque (3, 4).…”
mentioning
confidence: 99%
See 2 more Smart Citations